Small RNA mediated repression of subtilisin production in Bacillus licheniformis - Robert Hertel; Sandra Meyerjürgens; Birgit Voigt; Heiko Liesegang; Sonja Volland (Scientific Reports, 2017)
Abstract The species Bacillus licheniformis includes important strains that are used in industrial production processes. Currently the physiological model used to adapt these processes is based on the closely related model organism B. subtilis. In this study we found that both organisms reveal significant differences in the regulation of subtilisin, their main natural protease and a product of industrial fermentation processes. We identified and characterized a novel antisense sRNA AprAs, which represents an RNA based repressor of apr, the gene encoding for the industrial relevant subtilisin protease. Reduction of the AprAs level leads to an enhanced proteolytic activity and an increase of Apr protein expression in the mutant strain. A vector based complementation of the AprAs deficient mutant confirmed this effect and demonstrated the necessity of cis transcription for full efficiency. A comparative analysis of the corresponding genome loci from B. licheniformis and B. subtilis revealed the absence of an aprAs promoter in B. subtilis and indicates that AprAs is a B. licheniformis species specific phenomenon. The discovery of AprAs is of great biotechnological interest since subtilisin Carlsberg is one of the main products of industrial fermentation by B. licheniformis.